Symbolic Representations of Social Criticism in Us (2019) - Yudha, Bagus Putra Para (Cultural Narratives, 2025)
The evolution of media, particularly electronic and audio-visual media such as film, has provided an effective platform for conveying social criticism implicitly through symbolic elements. This research attempts to examine the social criticism signs in the Us (2019) film, by using Roland Barthes's semiotics theory and the concept of social criticism by David Harvey as the theoretical framework. The research method that used in this research is descriptive qualitative. The writer found there were four objects which become social criticism signs that the writer gets based on several objects that were attached to the Tethered throughout this film. The four objects are scissors, bunker, rabbit and the red color. In the analysis, the connotative signs of the four objects have an important role for understanding what forms of social criticism that experienced by the Tethered in this film. Scissors which have a connotative sign "get a freedom", is a symbol of social criticism regarding social oppression. Bunker which has a connotative sign "significant gap between upper-class and lower-class", is a symbol of social criticism regarding social and economic inequality. Rabbit which has a connotative sign "undervalued", is a symbol of social criticism regarding social discrimination. Red color which has a connotative sign "resistance", is a symbol of social criticism regarding resistance to social injustice. Based on the explanation, it can be concluded that these four signs have an important role to understand the social criticism that related to capitalism ideology in this film. This research contributes to the understanding of how films can serve as potent vehicles for social criticism by decoding implicit signs that symbolize complex socio-economic issues.